Edukasi Aplikasi Arang Sekam Dan Zpt Untuk Tanaman Pangan Masyarakat Desa Sidorejo - Handayani, Nurma; Ilyasin, Mochammad; Wandana, Tri; Susiani, Susiani; Wahyudi, Wahyudi; Lutfitasari, Bela Fitria Anita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Food plants are very important to be cultivated by rural communities as providers of food for survival. Sidorejo Village, Rowokangkung sub-district, Lumajang district was chosen as the village for the Lumajang University Kuliah Kerja Nyata (KKN) service. This KKN aims to emphasize the delivery of education to the Sidorejo village community on the importance of processing and using husk charcoal and organic liquid ZPT in food plants. The method used to realize an advanced Sidorejo village with food security is the first by making husk charcoal and organic liquid ZPT which is carried out by KKN students under the auspices of the Lumajang University LPPM. The husk charcoal and organic liquid ZPT produced will be given to the people of Sidorejo so that they can be applied to the community's food plants. The second method is outreach activities to the people of Sidorejo village regarding the importance of the benefits of husk charcoal and organic ZPT on the growth and development of food plants in Sidorejo village. Counseling to the people of Sidorejo through increasing the productivity of community food plants by utilizing materials that are easily found around the environment. The third method is the arrangement and maintenance of the continuity of Pawon Urip and the fourth is the stage. The results of the study were the creation of two products in the form of husk charcoal and organic liquid ZPT as well as increasing public knowledge on how to increase community food plant productivity and the movement to better maintain the survival of Pawon Urip Sidorejo plants so that they were growth and neatly arranged. Keywords: education, planting media, husk charcoal, ZPT, village.